2010
DOI: 10.1177/1043659609357631
|View full text |Cite
|
Sign up to set email alerts
|

Providing Care for Migrant Farm Worker Families in Their Unique Sociocultural Context and Environment

Abstract: This article highlights the Farm Worker Family Health Program's (FWFHP) strategies for providing care to migrant farm workers residing within a unique social and cultural context. The care provided by health professions students from a variety of disciplines extends and augments the work of the local migrant farm worker clinic that is pushed beyond capacity during peak growing and harvest times. Nursing's social responsibility to care for underserved populations is a guiding principle of the FWFHP and shapes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 8 publications
(7 reference statements)
1
30
0
1
Order By: Relevance
“…Among migrant farm workers, our study and others [27] found that the primary structural barrier for seeking care was not cost as described by urban participants, but losing time at work and subsequent earnings. In rural areas, offering screenings, education, and preventive care in mobile clinics after work hours has been shown to increase access to mainstream healthcare for rural male immigrants [2830]. …”
Section: Discussionmentioning
confidence: 99%
“…Among migrant farm workers, our study and others [27] found that the primary structural barrier for seeking care was not cost as described by urban participants, but losing time at work and subsequent earnings. In rural areas, offering screenings, education, and preventive care in mobile clinics after work hours has been shown to increase access to mainstream healthcare for rural male immigrants [2830]. …”
Section: Discussionmentioning
confidence: 99%
“…35 The challenges of accessing health care in rural areas have been reported, especially for those counties with a high proportion of minority populations. 3639 Poignantly, these studies suggest that residence in a rural area contributes to limited access to health care as a result of geographic distances as well as low income and education, with reduced frequency of patient-provider contacts, reduced early and correct diagnosis and treatment, ineffectual follow-ups and hence poorer control of the disease. 4043 Specifically, individuals are less likely to have regular checkups for IHD risk factors 44 and there may be lower compliance by health care providers to standardized therapies for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 They must navigate the health care system with often limited access to care, language and cultural barriers, worries of job loss, and resource barriers, such as a lack of transportation or child care due to inconvenient work hours. 2,7,9,10 Historically, MSFWs have lower health care utilization rates compared with the general US population 11 because of these issues.…”
Section: Introductionmentioning
confidence: 99%